Ectomycorrhizal fungi inoculation alleviates simulated acid rain effects on soil ammonia oxidizers and denitrifiers in Masson pine forest. (28th November 2018) - Li, Yan; Chen, Zhan; He, Ji‐Zheng; Wang, Qing; Shen, Congcong; Ge, Yuan
Summary: Acid rain can cause severe effects on soil biota and nutrient biogeochemical cycles in the forest ecosystem, but how plant‐symbiotic ectomycorrhizal fungi will modulate the effects remains unknown. Here, we conducted a full factorial field experiment in a Masson pine forest by simultaneously controlling the acidity of the simulated rain (pH 5.6 vs. pH 3.5) and the ectomycorrhizal fungi Pisolithus tinctorius inoculation (non‐inoculation vs. inoculation), to investigate the effects on ammonia oxidizers and denitrifiers. After 10 months, compared with the control (rain pH 5.6, and non‐inoculation), simulated acid rain (pH 3.5) reduced soil nutrient content, decreased archaeal amoA gene abundance and inhibited denitrification enzyme activity. Also, simulated acid rain altered the community compositions of all the examined functional genes (archaeal amoA, bacterial amoA, nirK, nirS and nosZ ). However, inoculation with ectomycorrhizal fungi under acid rain stress recovered soil nutrient content, archaeal amoA gene abundance and denitrification enzyme activity to levels comparable to the control, suggesting that ectomycorrhizal fungi inoculation ameliorates simulated acid rain effects. Taken together, ectomycorrhizal fungi inoculation – potentially through improving soil substrate availability – could alleviate the deleterious effects of acid rain on nitrogen cycling microbes in forest soils.